1997
DOI: 10.1016/s1074-7613(00)80511-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the B Lymphocyte Populations in Lyn-Deficient Mice and the Role of Lyn in Signal Initiation and Down-Regulation

Abstract: Lyn-deficient mice were generated to analyze the role of Lyn in B cell antigen receptor (BCR) signaling. These mice had a reduced number of peripheral B cells with a greater proportion of immature cells and a higher than normal turnover rate. Aged lyn-/- mice developed splenomegaly, produced autoantibodies, and had an expanded population of B lymphoblasts of the B1 lineage. Splenic B cells from young lyn-/- mice initiated early BCR signaling events, although in a delayed fashion. Unexpectedly, lyn-/- B cells e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

42
427
5
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 420 publications
(477 citation statements)
references
References 63 publications
42
427
5
2
Order By: Relevance
“…Although the precise mechanism(s) by which SFKs impact these functions in the HSC/P compartment are unclear, previous studies have demonstrated that these kinases in addition to both positively and negatively regulating functions in the same cell type can also antagonize the function of each other. For example, significant evidence exists to suggest that in B cells, early responses to BCR cross-linking are altered in Lyn −/− mice, supporting a role for Lyn in the initiation of signaling via the BCR [20,21,23]. Intriguingly, Lyn-deficient B cells are also hyperresponsive to anti-IgMinduced proliferation and demonstrate enhanced activation of mitogen-activated protein An alternate, but unlikely possibility to explain the increase in the number of relatively immature HSC/P cells in the BM of SFK −/− mice could be attributed to microenvironmental changes in these mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the precise mechanism(s) by which SFKs impact these functions in the HSC/P compartment are unclear, previous studies have demonstrated that these kinases in addition to both positively and negatively regulating functions in the same cell type can also antagonize the function of each other. For example, significant evidence exists to suggest that in B cells, early responses to BCR cross-linking are altered in Lyn −/− mice, supporting a role for Lyn in the initiation of signaling via the BCR [20,21,23]. Intriguingly, Lyn-deficient B cells are also hyperresponsive to anti-IgMinduced proliferation and demonstrate enhanced activation of mitogen-activated protein An alternate, but unlikely possibility to explain the increase in the number of relatively immature HSC/P cells in the BM of SFK −/− mice could be attributed to microenvironmental changes in these mice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, significant evidence exists to suggest that in B cells, early responses to BCR cross-linking are altered in Lyn −/− mice, supporting a role for Lyn in the initiation of signaling via the BCR [20,21,23]. Intriguingly, Lyn-deficient B cells are also hyperresponsive to anti-IgMinduced proliferation and demonstrate enhanced activation of mitogen-activated protein kinase and sustained calcium mobilization [21][22][23]26]. Hernandez-Hansen et al [32] have shown that dysregulated signaling in Lyn-deficient mast cells is due in part to enhanced Fyn activation, and a recent study by Hong et al [33] suggested that the Src kinase Hck regulates mast cell activation by suppressing activation of Lyn.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…B cells from mice deficient in Lyn (10)(11)(12), CD22 (13)(14)(15)(16), SHP-1 (17,18) exhibit a hyperreactive phenotype and produce autoantibodies. Indeed, Lyn-deficient mice demonstrate activation of autoreactive B cells and subsequent SLE-like symptoms, such as the production of anti-double-stranded DNA (anti-dsDNA) antibodies, splenomegaly, and glomerulonephritis (11,12).…”
mentioning
confidence: 99%